Effect of Dietary Supplementation of Crushed Soybean and Flaxseed on Estrus Attributes in Postpartum Crossbred Cows - Ratnaparkhi, Anand R; Deshmukh, Shyam G; Pawshe, Chaitanya H; Patil, Manoj S; Thorat, Milind G; Kuralkar, Shailendra V; Bhikane, Anil U; Waghmare, Sunil P (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
The objective of the present study was to examine the effect of dietary supplementation of crushed soybean and flaxseed on estrus attributes and preovulatory follicle size in postpartum cows. A total 20 postpartum crossbred multiparous cows from 2nd to 4th lactation with normal calving history were selected and randomly divided into two groups viz. Group 1 (T1) cows fed with roasted crushed soybean @10% of DM (300 g /100 Kg of body weight/day) till 50 and then after continued with crushed flaxseed @ 15% of DM (300 g /100 Kg of body weight/day) and group 2 (T2- without additional fat). Cows from both the groups were subjected to an ovsynch synchronization protocol on day 60 postpartum and observed for induced estrus response, time required for onset of induced estrus, intensity and duration of induced estrus. The diameter of preovulatory follicles was studied transrectaly with a linear-array 7.5 MHZ probe before the second buserelin acetate injection. The dietary supplementation of soybean and flaxseed influenced estrus response, intensity of estrus and time required for onset of induced estrus and duration of estrus however the difference was statistically non significant. At the same time the mean preovulatory follicle diameter was significantly higher in supplemented group.